2019
DOI: 10.3390/fermentation5010006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Seawater on Carotenoid Production and Lipid Content of Engineered Saccharomyces cerevisiae

Abstract: The use of seawater in fermentation can potentially reduce the freshwater burden in the bio-based production of chemicals and fuels. We previously developed a Saccharomyces cerevisiae carotenoids hyperproducer SM14 capable of accumulating 18 mg g−1 DCW (DCW: dry cell weight) of β-carotene in rich media (YPD). In this work, the impacts of seawater on the carotenoid production of SM14 were investigated. When using nutrient-reduced media (0.1× YNB) in freshwater the β-carotene production of SM14 was 6.51 ± 0.37 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…In another work, the effect of seawater was investigated (Guo et al . 2019 ). After cultivating the engineered S. cerevisiae strain in synthetic seawater combined with a high carbon-to-nitrogen ratio (C:N = 50), the authors reported a β-carotene production of 10.44 mg/g DCW.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another work, the effect of seawater was investigated (Guo et al . 2019 ). After cultivating the engineered S. cerevisiae strain in synthetic seawater combined with a high carbon-to-nitrogen ratio (C:N = 50), the authors reported a β-carotene production of 10.44 mg/g DCW.…”
Section: Discussionmentioning
confidence: 99%
“… 2017 ; Guo et al . 2019 ). Therefore, improving the lipid metabolism in S. cerevisiae might be a promising strategy to obtain higher titers of β-carotene when using an oily substrate as a carbon source.…”
Section: Discussionmentioning
confidence: 99%
“…Seawater fermentation is a sustainable approach that aims to reduce the water footprint of industrial biotechnology products. In addition to bioethanol production, a seawater fermentation approach has been recently proposed for other industrial biotechnology applications including production of succinic acid [38], baker's yeast [37] carotenoids [39], lipids [40], polyhydroxyalkanoates [41] and others [42]. Successful seawater-based biorefineries may be established as a coastal industry with direct access to clear and clean seawater.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of 0.5 M NaCl to the fresh water used in the preparation of nutrient media for engineered carotenoids producing S. cerevisiae strain increased the production of β-carotene by almost two times. An increase in the C:N ratio further improved carotenoid production by this strain [ 170 ]. The nitrogen sources were revealed as the main factors that most efficiently influenced the intracellular accumulation of carotenoids in yeast Rh .…”
Section: Biotechnologymentioning
confidence: 99%
“…mucilaginosa [ 169 , 171 ]. Metal ions (such as Ba, Fe, Mg, Ca, Zn, and Co) and especially some trace elements (such as Al, Zn, and Mn) are very important for carotenoids synthesis in various species of Rhodotorula [ 170 ]. A recent study has described the potential of the ascomycetous yeast species Y. lipolytica as a β-carotene-producing cell factory, reporting the highest titer of recombinant β-carotene produced to date [ 172 ].…”
Section: Biotechnologymentioning
confidence: 99%